ENHANCING THERAPEUTIC SECONDARY METABOLITE PRODUCTION BY COMPREHENSIVE BIOSTIMULANT INTEGRATION: HARMONIZING PLANT AND MICROBIAL EXTRACT: Significance of Microbial and Non-microbial Bio-stimulants - G.V., Anjali; S., Tamilselvi (SEAMEO BIOTROP, 2025)
HIGHLIGHTS- Integrative insights into Non-microbial and Microbial Biostimulants.- Focus on enhancing significant secondary metabolites and plant quality.- Comprehensive analysis of sustainable agricultural practices.- Future scope and positive research directions in Biostimulants.- Role of biostimulants in stress resilience. ABSTRACTIn recent decades, biostimulants have become recognized as organic alternatives for promoting sustainable agricultural practices, extensively applied across agriculture, horticulture, ornamental plants, and greenhouses. Unlike biofertilizers and biopesticides, biostimulants are derived from plants, animals, and microbes and classified by their chemical composition. They are primarily divided into non-microbial and microbial biostimulants. Non-microbial biostimulants include humic substances, seaweeds, Chitosan, protein hydrolysates, amino acids, and inorganic compounds, while microbial biostimulants consist of plant growth-promoting bacteria and beneficial fungi. This review paper consolidates the recent positive effects of biostimulants on sustainable agriculture and outlines potential research areas for the future. Biostimulants serve as biocontrol agents that promote plant growth and development, also reported to enhance the production of valuable industrial therapeutic secondary metabolites. Traditionally, plants with medicinal properties have been used for natural remedies, and biostimulants aim to elevate the secondary metabolite content in these therapeutic plants. Additionally, the significance of both microbial and non-microbial biostimulants is touched upon. A review of existing literature indicates that biostimulants significantly boost nutrient absorption, enhance resilience against abiotic stress, replenish nutrients, and improve soil quality.